SUPLEMENTAÇÃO DE AMINOÁCIDOS DE CADEIA RAMIFICADA E ÔMEGA 3: efeito clínico-nutricional no câncer. - SANTOS, Alexsandro Ferreira dos (2021)
Introduction: cachexia is a multifactorial syndrome of unquestionable clinical relevance, independent predictor of death, low therapeutic response, and worse quality of life (QOL). Objective: To analyze the effect of dietary supplementation with branched-chain amino acids (BCAA) and omega 3 fatty acids (W3) on cancer cachexia. Material and Methods: randomized, open clinical trial based on a systematic literature review and baseline data collection conducted between October 2018 and October 2019. The simple random sample consisted of 17 women with cervical cancer, aged 20 years or older, divided into two groups (supplemented with 14.4g / day of BCAA and Control - CTL). The protocol included supplementation for 56 days and guidelines for healthy eating. Were verified demographic and socioeconomic variables, and at the beginning and the end of supplementation were collected nutritional, cardiorespiratory, functional capacity, QOL, biochemical-inflammatory, clinical, and outcome variables. Statistical analysis was performed using SPSS® software. Was applied the Shapiro-Wilk, paired t / Wilcoxon, and t student / Man-Witney tests at a maximum significance level of 5%. Chapter I: were selected eight studies with individuals aged 18 to 84 years, samples from 27 to 332 participants (follow-up: 6-16 weeks). Outcomes evaluated: body weight, BMR, appetite, functional capacity, QOL, fatigue, IL6, TNF-α, C- reactive protein, albumin, pre-albumin, and survival. The description of the sample loss and the generation of a random sequence was present in 75.0% of the surveys. Chapter II: the sample comprised women aged 38.5 ± 5.6 years (BCAA, n = 8) and 41.1 ± 5.0 years (CTL, n = 9), white, with low education and income. There were statistically significant associations (p <0.05): reduced arm circumference and basal metabolic rate in the BCAA group compared to the CTL group; increase in TNF-α (165.7%) compared to baseline in the BCAA group and decrease in hematocrit in the CTL group. Chapter III: were evaluated 27 women cross- sectionally (age 40.2 ± 7.1 years), white, and from São Luís. Sarcopenia had a prevalence of 33.3%. Women with sarcopenia had a lower score for the Global and Functional Capacity domains when compared to non-sarcopenic women. Chapter IV: Was observed an average consumption of 62.6 ± 16.4g / day of proteins, 461.8 ± 232.1 mg/day of calcium, and 3.3 ± 3.1mcg / day of vitamin D. The lean mass was 21.3 ± 8.4 kg and the distance covered was 346.3 ± 77.6 m. There was a moderate, inverse, and statistically significant correlation between distance traveled and consumption of vitamin D. Chapter V: Protein consumption per meal (PCPM) for lunch and dinner reached the target of 20 to 30g. Regarding QOL, there was an inverse and statistically significant, and moderate correlation between FPP in the right hand and PCPM in the snack and FPP in the left hand and PCPM in the breakfast, respectively. Conclusion: supplementation with W3 is important for modulation of cachexia in cancer, other strategies include the adequacy of dietary consumption of vitamin D, calcium, and protein and attention to food consumption of protein in adequate quantity and distribution. Already the supplementation of BCAA alone, although attenuating the BMR, seems to increase the inflammatory condition and contribute to worse fat reserves.